COMPARISON OF FNA VS SURFACE SWAB CULTURE IN ISOLATING CORE FLORA IN RECURRENT TONSILLITIS - Khan, Inamullah; Ahmad, Sarfaraz; Chawala, Javed Akhtar (Journal of Ayub Medical College Abbottabad, 2012)
Background: Tonsillitis is one of the most common childhood afflictions. This prospective study was designed to explore the possible role of fine needle aspiration of recurrently inflamed tonsils in determining their core flora. Results: Seventy-seven patients at DHQ Hospital Haripur undergoing tonsillectomy for recurrent tonsillitis were included in the study. Colonies grown from fine needle aspirate and surface swab were compared with tonsillar core culture obtained after tonsillectomy. The pathogens isolated by fine needle aspiration culture were not greatly different from surface swab results in comparison to core isolates. Conclusion: The results of fine needle aspirate do not appear to confer any advantage over surface swab in representing core flora. These findings indicate no preferred clinical use for fine needle aspiration in the management of recurrent tonsillitis. Keywords: Fine needle aspiration (FNA), Culture, Tonsillitis